If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + 0) = 0.5(x + -3) Reorder the terms: (0 + y) = 0.5(x + -3) Remove the zero: (y) = 0.5(x + -3) y = 0.5(x + -3) Reorder the terms: y = 0.5(-3 + x) y = (-3 * 0.5 + x * 0.5) y = (-1.5 + 0.5x) Solving y = -1.5 + 0.5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -1.5 + 0.5x
| 8x^2=162 | | 4-5*n=21 | | (5b-4)-2(2b+1)=-2 | | 3(x+1)+2x=24 | | 4(x-0.66)=-18 | | 4k-7=k-10 | | -24+10=m-5 | | 7x-35=-2(-8x+4) | | 15=5-n | | 17=-5 | | 8x+1=-16 | | -6x+4(x-4)=-14 | | 72c=8 | | 26-(x-11)=-5(x+7) | | 5m+2m-5= | | x/-13=-40 | | w=2x^2-yz | | y=0.5x+1.5 | | 14*30+d=-196 | | (4+1)+2= | | 8y+2=21 | | 14+30+d=-196 | | 3=x(9-2x)(6-2x) | | 20=s-5 | | 7x+9+3x+1=8x-5 | | 8x-11=-5 | | 4/5n-7=17 | | 4log(x)-log(x^4)= | | 2(3x-2)=10x-13-7x | | 2x^3+3x^2-8x-4=0 | | 2n+-3n+-14=0 | | 4m-9=11 |